Efisiensi Pemasaran Bawang Merah di Desa Selopamioro, Kecamatan Imogiri Kabupaten Bantul, DIY - Nugroho, Mayang Ambarwati; Suswatiningsih, Tri Endar; Ismiasih (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
This research was conducted at Selopamioro village, Imogiri county, Bantul district. The tedious shallot marketing chain and a big difference in price affected by the marketers resulted in the farmers being left with dissatisfied prices. The purpose of this research is to understand the marketing pattern (channel), the price difference (margin) the efficiency of the marketing system and farmer’s share. The research volunteers of farmers and merchants surveyed with the snowball sampling method consisted of 25 farmers, 3 collectors, 3 wholesalers, and 3 small merchants. The marketing channel was discussed descriptively, meanwhile, the price difference (margin) and the marketing efficiency were explained quantitatively and supported by data and equations. The result showed that Selopamioro village used 2 different channels to market the shallot harvest which are, 1st channel: Farmers – Collectors – Wholesalers – Small Merchants – Consumers; and 2nd channel: Farmers – Collectors – Wholesalers – Consumers. The marketing efficiency in the village has proven to be “efficient”, where the highest efficiency comes from the 2nd channel with 2,84% compared 1st channel with 2,92%. The price difference (margin) on the 1st channel costs 21.500 Rp/Kg, while the 2nd channel costs 16.500 Rp/Kg. The score of Farmer's sharehas been “efficient” with the score of 1st channel is 48,81% and 2nd channel is 55,41%.